2018
DOI: 10.25134/erjee.v6i2.1254
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Students� Perspectives in Using Edmodo as an Educational Social Network

Abstract: Abstract:The integration of technology in education and the need to meet the requirements of the 21 st century learning lead educators to use online learning platforms. Edmodo is offered as one of learning platforms that could be used in EFL classroom. This research aims to investigate perception of undergraduate students on the use of Edmodo as an educational social network which has been implemented in the classroom. This study employed mix method design by involving 50 undergraduate students from a universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Similarly, [5] and [6] conducted conceptual research on the use of ICT, for instance, Edmodo and Facebook in the teaching and learning process. Second, [7], [8], [9], [10] and [11] who conducted the research on the perception or belief of using ICT either from the students' view or teachers' view. The results of those studies showed that the students and the teachers had a positive response toward ICT utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, [5] and [6] conducted conceptual research on the use of ICT, for instance, Edmodo and Facebook in the teaching and learning process. Second, [7], [8], [9], [10] and [11] who conducted the research on the perception or belief of using ICT either from the students' view or teachers' view. The results of those studies showed that the students and the teachers had a positive response toward ICT utilization.…”
Section: Introductionmentioning
confidence: 99%
“…However, teachers have willingness to bring technology in their classes to improve language teaching and learning. They realize that technology, if used effectively, can help teachers to explore their creativity and make the activities in the classroom authentic (Fitriah, 2018), give a new experience in teaching and learning, and help students to acquire 21st-century skills (Insani, Suherdi, & Gustine, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since learners today are 21st-century learners or digital natives as they possess high technology (Prensky, 2001;Trilling & Fadel, 2009), bringing technology into the classroom will meet the needs and increase their motivation especially in learning the language (Pazilah, Hashim, & Yunus, 2019;Ramadhiyah & Lengkanawati, 2019), and provide a great opportunity for them to study autonomously and collaboratively (Benson, 2001;Gilakjani, 2014;Insani et al, 2018;Rinekso & Kurniawan, 2020;Yeh & Lan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, learning strategies using computers and software applications as learning media are very popular with students. As a result, second and foreign language teachers have the options to use technology in the classroom (Insani, Suherdi, & Gustine, 2018). Therefore, technology is indicated as one of factors in the 21st century education.…”
Section: Dila Charisma and Khomarudinmentioning
confidence: 99%